2023
DOI: 10.3390/catal13020368
|View full text |Cite
|
Sign up to set email alerts
|

Stability Enhancement of Aldehyde Dehydrogenase from Anoxybacillus geothermalis Strain D9 Immobilized onto Seplite LX120

Abstract: Enzyme stability is regarded as an important criterion for an industrial biocatalyst. Aldehyde dehydrogenase (ALDH) from A. geothermalis strain D9 was previously reported to exhibit good thermostability. However, this enzyme is still not suited to use in harsh environments. In this current work, we aim to see the viability of ALDH in terms of stability when immobilized into Seplite LX120. The purified ALDH was successfully immobilized via physical adsorption at 4 h with 1.25 mg/mL enzyme loading. The immobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…showed the influence of storage temperature on proteins' stability. Overall, they concluded that storage temperatures of −20 to 4 °C and humidities of below 30% showed the best results for immobilized enzymes [39,40]. Here, the membranes were stored in PBS buffer solution for 7 days after ligand immobilization at 4 °C.…”
Section: Stability Of the Functionalized Membranes (Reusability And S...mentioning
confidence: 99%
“…showed the influence of storage temperature on proteins' stability. Overall, they concluded that storage temperatures of −20 to 4 °C and humidities of below 30% showed the best results for immobilized enzymes [39,40]. Here, the membranes were stored in PBS buffer solution for 7 days after ligand immobilization at 4 °C.…”
Section: Stability Of the Functionalized Membranes (Reusability And S...mentioning
confidence: 99%